2010
DOI: 10.1021/jf100957b
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Whey Protein Isolate−Pectin Complexes by Heat

Abstract: Protein-polysaccharide complexes formed under electrostatic associative conditions could have interesting functional properties. However, their stability over a wide range of pH limits their widespread application. The aim of this work was to determine the time-temperature combination required to stabilize whey protein isolate (WPI) and pectin (LMP) complexes formed at pH 4.5 to a further pH adjustment to 7. The effect of storage for 28 days at 4 degrees C was also evaluated. Stability was confirmed by quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…In other systems it has been shown that heating can stabilize protein-polysaccharide complexes to further pH adjustments (Jones, Decker, & McClements, 2009;Gentes et al, 2010). Regardless of the mechanism, the fact that thermal treatment enhances the solubility of SPI:PEC complexes is an important finding from the point of view of producing a shelf-stable food product that could be pasteurized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other systems it has been shown that heating can stabilize protein-polysaccharide complexes to further pH adjustments (Jones, Decker, & McClements, 2009;Gentes et al, 2010). Regardless of the mechanism, the fact that thermal treatment enhances the solubility of SPI:PEC complexes is an important finding from the point of view of producing a shelf-stable food product that could be pasteurized.…”
Section: Discussionmentioning
confidence: 99%
“…We also consider the effects of thermal processing on these complexes. Some previous reports have documented that proteinpectin complexes may be stabilized by heat (Gentes, St-Gelais, & Turgeon, 2010), however no description is available for soy proteinpectin complexes. Finally, we demonstrate similar functionality can be achieved in SPI:PEC complexes at product produced at pilot scale.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions can be adopted to obtain different functionalities. For instance, Co-soluble polysaccharides can be used to improve heat stability of protein-enriched beverage (Gentès et al, 2010), protein/polysaccharide nanoparticles formed based on associative interaction can be used as carrier of bioactive compounds with improved bio-availability (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This led to the formation of aggregated protein molecules. The second step was lowering of the pH to the isoelectric point of the whey proteins (pH 5.2-5.4), [58][147] which resulted in phase separation and spontaneous restructuring of the proteins at the molecular level. When shearing or mixing was applied during incubation, forced-assembly also played a role during MP formation.…”
Section: Chaptermentioning
confidence: 99%
“…In the first step, whey proteins are turned into reactive aggregates by mildly heating a protein solution with a concentration lower than the critical gelation concentration (11-12%), [7][90] at low ionic strength; and a pH above or below its isoelectric point (pH 5.2-5.4). [58][ 147] This results in the formation of protein aggregates with a hydrodynamic diameter of about 80 nm.…”
Section: Introductionmentioning
confidence: 99%